2010
DOI: 10.4061/2011/431320
|View full text |Cite
|
Sign up to set email alerts
|

E22Δ Mutation in Amyloid β‐Protein Promotes β‐Sheet Transformation, Radical Production, and Synaptotoxicity, But Not Neurotoxicity

Abstract: Oligomers of 40- or 42-mer amyloid β-protein (Aβ40, Aβ42) cause cognitive decline and synaptic dysfunction in Alzheimer's disease. We proposed the importance of a turn at Glu22 and Asp23 of Aβ42 to induce its neurotoxicity through the formation of radicals. Recently, a novel deletion mutant at Glu22 (E22Δ) of Aβ42 was reported to accelerate oligomerization and synaptotoxicity. To investigate this mechanism, the effects of the E22Δ mutation in Aβ42 and Aβ40 on the transformation of β-sheets, radical producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…37, 38, 39, 40, 41, 42, 43 In contrast to these initial in vitro findings, subsequent work, including our own recent study with highly pure recombinant peptide preparations, demonstrated that both E22Δ Aβ40 and E22Δ Aβ42 readily formed amyloid fibrils in vitro . 20, 24, 44 Based on these in vitro findings, we hypothesized that E22Δ Aβ40 and E22Δ Aβ42 would, at least in principle, also form amyloid fibrils in vivo . Indeed, aged E22ΔAβ mice accumulated detergent-insoluble Aβ and showed thioflavin S and Congo red-positive amyloid deposits in leptomeningeal cortical and—more pronounced—cerebellar vessels; in contrast to the recently published E693Δ mouse model, which completely lacked extracellular amyloid deposition even at an age of 24 months, 22 E22ΔAβ mice overexpress human APP at levels comparable to those in the Tg2576 mouse line, and the introduction of the Swedish double mutation results in an additional increase in total Aβ levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37, 38, 39, 40, 41, 42, 43 In contrast to these initial in vitro findings, subsequent work, including our own recent study with highly pure recombinant peptide preparations, demonstrated that both E22Δ Aβ40 and E22Δ Aβ42 readily formed amyloid fibrils in vitro . 20, 24, 44 Based on these in vitro findings, we hypothesized that E22Δ Aβ40 and E22Δ Aβ42 would, at least in principle, also form amyloid fibrils in vivo . Indeed, aged E22ΔAβ mice accumulated detergent-insoluble Aβ and showed thioflavin S and Congo red-positive amyloid deposits in leptomeningeal cortical and—more pronounced—cerebellar vessels; in contrast to the recently published E693Δ mouse model, which completely lacked extracellular amyloid deposition even at an age of 24 months, 22 E22ΔAβ mice overexpress human APP at levels comparable to those in the Tg2576 mouse line, and the introduction of the Swedish double mutation results in an additional increase in total Aβ levels.…”
Section: Discussionmentioning
confidence: 99%
“…9 Consistent with these findings, synthetic E22Δ Aβ42 potently inhibited hippocampal long-term potentiation 9, 19 and induced synapse loss in mouse hippocampal slices. 20 Further cell culture experiments and results from the recently reported E693Δ transgenic mouse model revealed enhanced accumulation of intraneuronal Aβ oligomers as a prominent feature of the Osaka APP mutation. 21, 22, 23 E693Δ transgenic mice start to accumulate intraneuronal Aβ aggregates at an age of 8 months and are completely devoid of extracellular amyloid deposits up to an age of 24 months.…”
Section: Introductionmentioning
confidence: 91%
“…21,22 Other experimental measurements indicate that the E22Δ mutation does not increase the toxicity of either the Aβ40 or Aβ42 peptides but instead only inhibits synaptic function more than the wild-type Aβ alloforms. 14,23,24 Moreover, experimental measurements have reported conflicting trends for the impact of the E22Δ mutation on the aggregation rates of the Aβ peptide. While some studies report an increase in oligomerization but not fibrillization for the E22Δ mutant-type Aβ in comparison to the wild-type, other studies do report that the rate of fibrillization is increased upon E22Δ mutation.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…22 In contrast, Suzuki et al reported that neither E22Δ mutant-type Aβ40 nor E22Δ mutant-type Aβ42 displays increased neurotoxicity for primary rat cortical neurons utilizing MTT and LDH assays in their experiments. 23 On the other hand, several experiments presented that the E22Δ mutation of Aβ inhibits the synaptic function of neurons. 14,21,23,24 Interestingly, Suzuki et al proposed that the E22Δ mutanttype Aβ42 inhibits synaptic function more than the E22Δ mutant-type Aβ40 peptide.…”
mentioning
confidence: 99%
“…40 Mori, Tomiyama, and colleagues reported that intraneuronal Aβ oligomers induce neuronal death through enhancement of endoplasmic reticulum stress endosomal/lysosomal leakage and mitochondrial dysfunction. 41 The relevance of this mutation to toxic turn formation in the progression of AD remains to be investigated.…”
Section: ■ Conclusionmentioning
confidence: 98%